(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
Sponges are, beside of scleractinian corals the most abundant reef building organisms in Norian-Rhaetian reefs or reefal limestones of Iran. The sponge fauna from a small biohermal reef structure near the town of Yazd is described. Tectonically it belongs to the so called "Yazd-Block". All described species are hypercalcified sponges, only one species of chambered hexactinellid was found. The chambered species Welteria lutensis n. sp. is described.